👤

Hay Merci De M'Aider
Factoriser :
16 (-8x - 8)² - 9 (-8x + 8)²
(5x + 1) (2x + 3) + (5x + 1) (x - 2) - (7x - 4) (10x + 2)


Répondre :

Réponse :

Bonsoir

Explications étape par étape

Factoriser :

16 (-8x - 8)² - 9 (-8x + 8)²

= 4²(-8x - 8)² - 3²(-8x + 8)²

= [2(-8x - 8) - 3(-8x + 8)][2(-8x - 8) + 3(-8x + 8)]

= (-16x - 16 + 24x - 24)(-16x - 16 - 24x + 24)

= (8x - 40)(-40x + 8)

= 8(x - 5) * 8(-5x + 1)

= 64(x - 5)(-5x + 1)


(5x + 1) (2x + 3) + (5x + 1) (x - 2) - (7x - 4) (10x + 2)

= (5x + 1)[2x + 3 + x - 2 - 2(7x - 4)]

= (5x + 1)(3x + 1 - 14x + 8)

= (5x + 1)(-11x + 9)